Outermost Small Islands in Indonesia for Quarantine Area and Livestock Development - Endang Sutedi; Iwan Herdiawan; Eko Handiwirawan (Indonesian Center for Animal Research and Development, 2017)
Indonesia has about 17,506 islands consisting of large and small islands. Outermost small islands are direct boundary of Indonesia with neighboring countries. These outermost islands have the potency to be used as quarantine area and for livestock development, especially beef cattle in order to support the development of food security of meat. Some of outermost islands are Jemaja island in Riau Province, Singkil island in Aceh Province and Naduk island in Bangka Belitung Province. Criteria to determine quarantine area and livestock development are availability of natural resources (fresh water and forage), free of contagious diseases, human resources, market access, and transportation. This paper describes about the condition and forage availability in those three islands and their surrounding area. Those islands have potential variety of forage with different carrying capacities. Type of grass that has been adapted in the outermost islands are Paspalum conjugatum, Axonopus compressus, Cynodon dactylon, Cynodon plectostachyus, and Panicum repens.